2019
DOI: 10.17676/hae.2019.35.34
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Technological Parameters of ISOBUS System Supported Machinery Management

Abstract: ISO organization in early 90s defined an industry standard for the communication protocol among electronic devices of different manufacturers of agricultural machines. After that, all of the market actors recognised that this technology would be very important for agricultural electronics. The appearance of ISOBUS products in the market was in the mid-2000s. ISOBUS description could be found in ISO-11783. It is a very complex and large electronics protocol standard based on CAN and SAE-J1939 standards, extende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We have accomplished the examinations by taking power-machines from different quality and cost levels as base. Through this we have showed that not only the size of the farms effects the amount of the operational costs, but the standard of mechanization too [4].…”
Section: Introductionmentioning
confidence: 80%
“…We have accomplished the examinations by taking power-machines from different quality and cost levels as base. Through this we have showed that not only the size of the farms effects the amount of the operational costs, but the standard of mechanization too [4].…”
Section: Introductionmentioning
confidence: 80%
“…Through this we have showed that not only the size of the farms effects the amount of the operational costs, but the standard of mechanization too [4].…”
mentioning
confidence: 80%